Proteomic Sequencing of Stellate Ganglions in Rabbits With Myocardial Infarction - Cheng, Lijun; Wang, Xinghua; Chou, Hongda; Liu, Tong; Fu, Huaying; Li, Guangping (Frontiers in Physiology, 2021)
The stellate ganglion (SG) of the autonomic nervous system plays important roles in cardiovascular diseases (CDs). Myocardial infarction (MI) is associated with sustained increasing cardiac sympathetic nerve activity. Expressions and functions of proteins in SG tissue after MI are remaining unclear. The present study is to explore the expression characteristics of proteins in SGs associated with MI. Japanese white big-ear rabbits (n=22) were randomly assigned to control group and MI group. MI model was established by left anterior descending coronary artery ligation and confirmed by serum myocardial enzymes increasing, 2,3,5-triphenyltetrazolium (TTC) staining and echocardiography. The expressions of proteins in rabbit SGs after MI were detected by tandem mass tags (TMT) quantitative proteomic sequencing. There were 3043 credible proteins were predicted in rabbit SG tissues and 383 differentially expressed proteins (DEPs) including 143 up-regulated and 240 down-regulated proteins. Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed that the DEPs involved in adrenergic signaling in cardiomyocytes; positive regulation of ERK1 and ERK2 cascade and other biological processes. Three kinds of proteins directly correlated to CDs were selected to be validated by the subsequent western blot experiment. The present study firstly identified the proteins’ characterization in rabbit SG after MI, which laid a solid foundation for revealing the mechanism of SG’s roles on MI process.